Efeitos da necessidade de fechamento cognitivo na avaliação do consumidor sobre o out-of-stock em lojas varejistas - Lopes, Eliane Herrero (2021)
Out-of-stock is the momentary lack of product at a point of sale, a phenomenon that causes concern and loss for merchants, as it could result in consumers reacting in ways such as complaints, replacing the missing product, or abandoning the store. Several studies identified consumer reactions to out-of-stock (OOS) under the focus of assessing the purchase situation and the missing product. However, this thesis sought to investigate the influence of the consumers’ evaluations of retailers in these scenarios, adding an individual’s dispositional characteristic as a factor in the process. Thus, the main objective of this thesis is to identify, from the consumer assessment and their purchase intention, the retailer’s most effective failure recovery strategies in out-of-stock scenarios, studying the moderation of the need for cognitive closure (NFCC). This dissertation is divided into four experimental studies: 1) influence of out-of-stock on the consumer’s evaluation of the retailer; 2) influence of out-of-stock of target and non-target products in the intention to replace the store; 3) out-of-stock and the influence of the need for individual cognitive closure in the purchase intention; and 4) the effectiveness of failure recovery strategies, with the moderation of the need for cognitive closure in out-of-stock scenarios. The results showed that OOS influences the attitudinal responses of consumers, who evaluate negatively high levels of OOS (40% or more) and have less intention to buy in these scenarios. Also, having an OOS target product (versus non-target) negatively influences the evaluation and purchase intention and increases the consumer’s intention to replace the retailer. High levels of NFCC negatively influence the intention to buy in general, especially when OOS is a target product to purchase. Finally, the results showed the most efficient strategies for retailers to recover from OOS failure, both in subjects with high and low NFCC.